Non-Institutional and Grassroots Prescriptivism for Slovenian - Zgonc, Matjaž (Slovenski jezik / Slovene Linguistic Studies, 2023)
The current SP 2001 with supplementary infrastructure (Fran portal, Jezikovna Svetovalnica) has the highest normative authority for the Slovenian speech community. Still, non-institutional usage guides have been appearing in Slovenia, addressing the issues of complicated rules and protracted searches. Since they do help speakers of Slovene resolve some usage problems, two forms of prescriptivism for Slovenian were surveyed: non-institutional prescriptivism and grassroots prescriptivism. Non-institutional prescriptivism is an anglophone invention appearing mostly in book form and is typically based on an author’s sense of style. Grassroots prescriptivism is a relatively novel phenomenon which consists of internet users interacting to solve one another’s usage problems without necessarily being language professionals. For Slovene, it was discovered that several books were published that resemble usage guides. Three have been researched and it was discovered that Pravipis by Aleksandra Kocmut most closely resembles a prototypical usage guide. Interestingly, the authors all cede normative authority to SP 2001, an institutional guide. Most of grassroots prescriptivism is carried out in specific Facebook groups in which their members rapidly respond to posted usage problems. Among other things, it was discovered that grassroots prescriptivism responds to usage problems more quickly while institutional guidace does so in a more reliable and informed manner.